Los países pequeños en la economía mundial - Kadar, Bela (Estudios Internacionales, 1971)
Considering the boom in the study of economic development and development strategies in the last quarter century, this paper examines the correlations of economic potential and development from the point of view of small countries in the world economy, and also the development alternatives appropriate to them. Among others, the following issues are analyzed: the expansion of the scale of economic activities and the extent to which this influences the modern process of growth; where and how are the advantages and disadvantages of small countries, and what are the characteristic features of them, given the current circumstances of the world economy; what are the economic-political measures, the forms of economic management and the structures that can compensate for the disadvantages arising from the small size of each country.